2015
DOI: 10.1021/acschembio.5b00754
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Synchrotron Fourier Transform Infrared Spectroscopy and Single Molecule Super Resolution Microscopy for the Detection of Composition and Ultrastructure Alterations in Single Cells

Abstract: Single molecule localization microscopy (SMLM) and synchrotron Fourier transform infrared (S-FTIR) spectroscopy are two techniques capable of elucidating unique and valuable biological detail. SMLM provides images of the structures and distributions of targeted biomolecules at spatial resolutions up to an order of magnitude better than the diffraction limit, whereas IR spectroscopy objectively measures the holistic biochemistry of an entire sample, thereby revealing any variations in overall composition. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Thus, to directly detect and quantify cellular MT filament bundling induced by P3, we utilized d STORM super-resolution imaging, which overcomes the diffraction limit by detecting unperturbed emission point spread functions from single molecules, enabling highly precise spatial localization of the emitting fluorophores. Analysis used cell fixation and immunostaining protocols known to preserve MT integrity, which we have been used previously to visualize individual MTs 38 39 40 , with d STORM measurements made using a custom-built super-resolution widefield microscope that can achieve single molecule localization precisions better than 10 nm, and spatial resolution down to 20 nm 41 . Detailed images of MT architecture were acquired with sufficient resolution to differentiate closely associated MTs (presumed to be bundles, see below) from individual MTs which are tens of nanometers apart but occupy the same diffraction limited area and so cannot be resolved using conventional light microscopy (see supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, to directly detect and quantify cellular MT filament bundling induced by P3, we utilized d STORM super-resolution imaging, which overcomes the diffraction limit by detecting unperturbed emission point spread functions from single molecules, enabling highly precise spatial localization of the emitting fluorophores. Analysis used cell fixation and immunostaining protocols known to preserve MT integrity, which we have been used previously to visualize individual MTs 38 39 40 , with d STORM measurements made using a custom-built super-resolution widefield microscope that can achieve single molecule localization precisions better than 10 nm, and spatial resolution down to 20 nm 41 . Detailed images of MT architecture were acquired with sufficient resolution to differentiate closely associated MTs (presumed to be bundles, see below) from individual MTs which are tens of nanometers apart but occupy the same diffraction limited area and so cannot be resolved using conventional light microscopy (see supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…High resolution microscopy is also mostly performed on aldehyde-fixed cell monolayers. However, as these cell monolayers cannot typically withstand antigen retrieval, we recommend the use of methanol fixation for high resolution immunofluorescence of necroptosis; even though methanol fixation can be sub-optimal for both the retention of certain biomolecules 54 and the preservation of cellular architecture 55,56 . Indeed, all but one of the antibodies (source: Cell Signaling Technology clone D6W2T) in the suggested toolbox in Fig.…”
mentioning
confidence: 99%
“…The reasons for this are believed to be twofold: first, coagulant fixatives such as TCA are known to result in cytoplasmic flocculation (Eltoum et al ., ) and second, dehydration of cells results in a loss of hydrogen bonding that may cause bonding between molecules that would not normally interact, resulting in the fusion of cellular organelles (Wolkers et al ., ). Recent research has since shown that these often considered pervasive fixation artefacts can be investigated, monitored and minimised using correlative complementary IR spectroscopy and single molecule localisation microscopy techniques (Whelan & Bell, ). At the time, disruption and homogenisation of cell organelles was not too detrimental to the aims of the primary study.…”
Section: Discussionmentioning
confidence: 99%